BCS Computer Arts Society Celebrates 50 Years. (21st August 2019) - Unknown
Abstract: As the swinging 60s drew to a close, the Beatles released Abbey Road, Concorde made her maiden fl ight from France and the the world's fi rst microprocessor was invented, the Computer Arts Society held its very fi rst exhibition